WASTE MANAGEMENT DURING A PANDEMIC (CASE STUDY: STUDENT OF ECONOMICS AND BUSINESS FACULTY DIPONEGORO UNIVERSITY AND TADULAKO UNIVERSITY) - Hastarini Dwi Atmanti; Juliana Kadang (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: Many actions were done by students online during the Covid-19 pandemic. This activity generates waste as well. The aim of this paper is to learn more about how students dealt with waste during the pandemic. The research was conducted using descriptive analysis. Samples were taken purposively by students of the Economics and Business Faculty Diponegoro University and students of the Economics and Business Faculty Tadulako University. According to the findings of the study, the majority of students who responded do not appropriately manage waste. This situation requires attention since students can be agents of change for the better in order to ensure the sustainability of the environment. Keywords: waste management, pandemic, student, environment